Lo ferm voler qu’el cor m’intra (Mantichora. Italian Journal of Performance Studies, 2025)
The composition Lo ferm voler qu’el cor m’intra, attributed to Arnaut Daniel, sanctions the birth of the lyric sestina, which is still surrounded by an aura of excessive technical-formal sacrality that does not allow its essence to be understood. In fact, the sestina presents compositional peculiarities that must first be returned to the type of fruition that the troubadour performance implied (i.e. oral and not written) (Mayo 2012). Moreover, the significance of this performance is not to be attributed to contrivances for their own sake, but to the composer’s precise intention to reintroduce into the performance an unexpected passion of his: that of gambling (Marchis 2009). Here, rhymes and notes actually become the dice with which Arnaut plays, and the sestina is transformed into a permutation of possible random combinations (Canettieri 2023). This is made even more effective by the particular melodic pattern (Rossell 2015) and the phonic-semantic characteristics of the text, which give the performance a characteristic semantic-conceptual poignancy.